2011
DOI: 10.1590/s0036-36342011000500006
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias de la mortalidad por cáncer de mama en México, 1980-2009

Abstract: Breast cancer has become an important health risk for women worldwide.The important growth of breast cancer-related deaths within those caused by malign tumors throughout the globe went past the 460 000 in 2008,becoming the deadliest disease worldwide. Demographic changes and lifestyles have modified the population exposure to risk factors of maladies such as cancer, and since 1980 breast cancer mortality has remained on an upward tendency, surpassing cervical cancer in 2006. After analyzing mortality rates al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
8

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
0
11
1
8
Order By: Relevance
“…Recently, HPV vaccinations have been included in national vaccination campaigns [15]; therefore, this favorable tendency towards decreasing mortality due to cervical cancer is likely to continue in the future. Although different to our results, the recent increase in breast cancer mortality of Mexican woman has been also observed previously in woman ≥65 year-old [16]. These data indicated that much effort is needed to reverse the significant increase in mortality due to breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, HPV vaccinations have been included in national vaccination campaigns [15]; therefore, this favorable tendency towards decreasing mortality due to cervical cancer is likely to continue in the future. Although different to our results, the recent increase in breast cancer mortality of Mexican woman has been also observed previously in woman ≥65 year-old [16]. These data indicated that much effort is needed to reverse the significant increase in mortality due to breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…It was noted that, although the number of deaths from this cause had gradually increased over time nationwide, in some states of the country this increase was extremely significant. 27 In Portugal, there was a change in breast cancer mortality since the beginning of the 1990s, with sharper declines in districts with higher mortality rates. The authors considered that improvements in early detection of the disease and access to effective treatments could justify this change, but the characteristics of the access, screening and care of patients in different Portuguese districts would be essential for understanding differences observed at regional level.…”
Section: Discussionmentioning
confidence: 99%
“…3,34 However, this study is one of the first that takes into account the insurance scheme, which gives an added value to generate an hypotheses about the differential impact of the inclusion of comprehensive BC treatment between FPGC populations with and without social security.…”
Section: Discussionmentioning
confidence: 99%
“…Although Mexico is one of the 10 countries with the lowest incidence and mortality rates in the Americas, 1,2 standardized mortality rates per 100 000 women aged 25 years and older in 2009 ranged between 9.10 and 26.69 in the individual states. 3 A trend of increasing standardized mortality rates, which rose from 11.7 to 17.0 deaths per 100 000 women aged 25 years and over between 1980 and 2009, was observed. 3 There are no figures available on the incidence of BC because Mexico does not have a histopathological cancer registry.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation